Twee versoenbare konstrukte in resente historiese Jesus-navorsing, Deel II: Andries van Aarde 1 - Wyk, D. J. C. van (Hervormde teologiese studies, 2000)
Two compatible constructs in current historical Jesus re-search, Part II: Andries van Aarde. In Part I, John Dominic Crossan's proile of the historical Jesus was discussed. This article focuses on Andries van Aarde's view. According to Van Aarde, Joseph the father of Jesus should historically be seen as a legendary figure and that Jesus grew up fatherless. The stories of Jesus, virginal conception are myths. However, they reflected an historical context of the separation between the post-Easter synogogical movement and the Jesus movement. The article also discusses Van Aarde's view on the resurrection narratives, the contininuity and discontininuity between Jesus, and earliest Christianity and his view on canon and dogma. It concludes with a comparison between Corssan,s and Van Aarde's perspectives.